MANAJEMEN KESISWAAN DALAM PERSPEKTIF ALQUR’AN DAN IMPLEMENTASINYA DI SEKOLAH - MU’IZZUDDIN, MOCHAMAD; IDRIS, AHMAD; NURHAYATI, NENG (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2024)
Student management is a crucial aspect of education, focusing on the management of human resources and the development of students' character. From the perspective of the Qur'an, student management is not only viewed from an administrative standpoint but also from moral and spiritual aspects. This concept emphasizes the values of justice, honesty, and responsibility as outlined in Islamic teachings. The Qur'an stresses the importance of education as a means to shape individuals of high quality, both academically and morally. Effective student management in this context should involve developing students' potential, providing a positive learning environment, and implementing teaching methods that align with Islamic principles. By combining modern managerial approaches with the values of the Qur'an, it is hoped that the educational process can produce a generation that is not only intellectually intelligent but also possesses high moral integrity. This research aims to explore the concept of student management from the Qur'anic perspective and its implications for educational practices in Islamic educational institutions. ABSTRAKManajemen kesiswaan merupakan aspek penting dalam dunia pendidikan, yang berfokus pada pengelolaan sumber daya manusia dan pengembangan karakter siswa. Dalam perspektif Al-Qur'an, manajemen kesiswaan tidak hanya dilihat dari segi administratif, tetapi juga dari aspek moral dan spiritual. Konsep ini mengedepankan nilai-nilai keadilan, kejujuran, dan tanggung jawab yang tertuang dalam ajaran Islam. Al-Qur'an menekankan pentingnya pendidikan sebagai sarana untuk membentuk pribadi yang berkualitas, baik secara akademis maupun akhlak. Pengelolaan kesiswaan yang efektif dalam konteks ini harus melibatkan pengembangan potensi siswa, penyediaan lingkungan belajar yang positif, serta penerapan metode pengajaran yang sesuai dengan prinsip-prinsip Islam. Dengan memadukan pendekatan manajerial modern dan nilai-nilai Al-Qur'an, diharapkan proses pendidikan dapat menghasilkan generasi yang tidak hanya cerdas secara intelektual, tetapi juga memiliki integritas moral yang tinggi. Penelitian ini bertujuan untuk menggali konsep manajemen kesiswaan dalam perspektif Al-Qur'an dan implikasinya bagi praktik pendidikan di lembaga-lembaga pendidikan Islam.